2012
DOI: 10.1111/j.1365-2702.2012.04320.x
|View full text |Cite
|
Sign up to set email alerts
|

Bed and shower baths: comparing the perceptions of patients with acute myocardial infarction

Abstract: The perceptions of patients receiving baths are very important to guiding nursing care and developing strategies to minimise patient dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
(26 reference statements)
0
13
0
1
Order By: Relevance
“…However, the most traditional bed bath with water, soap, towels and wash basins is argued to have some adverse outcomes. First of all, regarding stakeholder experiences, patients often feel dependent and uncomfortable during the traditional bed bath [8]. Therefore, the bed bath can trigger aggressive and agitated behaviors, especially if patients are cognitively impaired [3, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most traditional bed bath with water, soap, towels and wash basins is argued to have some adverse outcomes. First of all, regarding stakeholder experiences, patients often feel dependent and uncomfortable during the traditional bed bath [8]. Therefore, the bed bath can trigger aggressive and agitated behaviors, especially if patients are cognitively impaired [3, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This association was also observed in other studies both in patients with heart disease and in other groups. (19)(20)(21) Regarding the short-term outcomes analyzed, it could not be demonstrated that anxiety is a predictor of the occurrence of non-fatal arrhythmias. Although our initial hypothesis has not been confirmed, there is underlying pathophysiological foundation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparing the two bed-bath applications, researchers found that the disposable bed-bath method required less time, fewer nurses, and was less expensive than the traditional method [3,9,16,17]. Other studies concerning the cost analysis of disposable wipes were determined cost-effective for ensuring infection control when compared to the traditional method [14,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…In ICUs, patients need specialized medical treatment and nursing care [1].Coyer et al [2] stated that most nursing interventions in the ICU included the promotion of personal hygiene, patient comfort, positioning, management of stressors, pain management, and sedation management. Maintaining personal hygiene is imperative for an individual's health and wellbeing and nurses should ensure that the hygiene needs of the patients in their care are adequately met [3,4]. Nurses maintain the personal hygiene needs (especially bed baths) of ICU patients because of their limited level of independence and self-care ability [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation